-77-v=v-3

Simple and best practice solution for -77-v=v-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -77-v=v-3 equation:



-77-v=v-3
We move all terms to the left:
-77-v-(v-3)=0
We add all the numbers together, and all the variables
-1v-(v-3)-77=0
We get rid of parentheses
-1v-v+3-77=0
We add all the numbers together, and all the variables
-2v-74=0
We move all terms containing v to the left, all other terms to the right
-2v=74
v=74/-2
v=-37

See similar equations:

| x+2=6+(3x) | | 12x3-26x-14=0 | | (4a-4)=(a+6) | | 6=d9 | | (4r+7)=(2r-3) | | 7x+7(x-2)=56 | | 11x-5=12x-11 | | 2x+4x=8x+10 | | 11x–5=11x–5 | | 11t–5=11t–5 | | 2+-x=15 | | 1/5x+5=12 | | 4x+27=3x+49 | | F(x)=14-0.5×30 | | -7=5+u/2 | | .5(r+2.5)=3 | | 9/7=-2/b | | 2q+10=12 | | 2x+3=-3x-12 | | 24=14y-8 | | 5/3x+-4/3x+-1=8 | | 21y=-42 | | 31.25(p+5)=750 | | 6x-(7)=13+2x | | 7c-2c+2c-2c=5 | | 15q-11q-3q=17 | | 8h+18h+-16h+-6h+13h=-17 | | 20q-18q+2q+q-q=16 | | 3x-15=2x(x-5) | | -5(1+m)=-5-4m | | 17v-17v+2v=14 | | a+4a+3a-5a=6 |

Equations solver categories